Numerical simulation of flow around circular cylinder near a plane wall: Effects of wall proximity, boundary layer and reynolds number - Grioni, Mauro (2023)
The cylindrical structures in close proximity to a solid surface have diverse and numerous applications within current engineering. While the flow dynamics around an isolated circular cylinder located in a uniform flow are reasonably well understood, this is not the case when the cylinder is positioned near a plane wall. This particular configuration is studied using computational fluid dynamics (CFD) through the Fluent code, which implements the finite volume method. For this purpose, a two-dimensional and transient flow is carry out using the SST-SAS turbulence model. The effects of changing the separation (G) between the cylinder (with diameter D) and the wall are analyzed for different Reynolds numbers and different boundary layer thicknesses. The lift and drag coefficients and the behavior of vortex shedding (Strouhal number, St) are examined. The numerical results are compared with values available in the literature from experimental wind tunnel tests, showing that both the drag and lift coefficients strongly depend on the separation ratio (G/D) and are affected by the boundary layer thicknesses.